2019
DOI: 10.24036/ld.v13i2.106880
|View full text |Cite
|
Sign up to set email alerts
|

Deixis in Donald Trump’s Speech to Un General Assembly

Abstract: The objective of the study is “to describe how deixis are used in Donald Trump’s Speech to UN General Assembly”. The design of this study is a descriptive qualitative design. Source of data collection in this research is the text of Donald Trump’s Speech to UN General Assembly done in 2018. After collecting data, the researcher found and selected data that the most of sentences or words have deixis types. After the data were reduced, then the next step is to display data, then, presenting data. Data summarizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Meanwhile, his use of social deixis was much less frequent, only to express respect and indicate the uniqueness of his audience when meeting the Arab leaders. Another study by Retnowaty (2019) revealed that the use of personal deixis was more frequent than other deixis in Donald Trump's speech in the UN General Assembly. He mostly used we to refer to the USA to portray himself as a part of USA society.…”
Section: Variousmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, his use of social deixis was much less frequent, only to express respect and indicate the uniqueness of his audience when meeting the Arab leaders. Another study by Retnowaty (2019) revealed that the use of personal deixis was more frequent than other deixis in Donald Trump's speech in the UN General Assembly. He mostly used we to refer to the USA to portray himself as a part of USA society.…”
Section: Variousmentioning
confidence: 99%
“…Astuti (2019) analyzed how Trump used personal deixis in his 2016 campaign speeches and found that I and we were used to promoting himself while they and she were employed to attack his opponents. Meanwhile, Retnowaty (2019) found that Trump dominantly used personal deixis in his speech in the United Nations General Assembly. It could be concluded from the two studies that the use of personal deixis becomes one of Donald Trump's strategies in delivering political speeches.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known that social deixis is a deixis that refers to the status and relation between participants (Levinson, 1983). In social deixis also exposes the social rankings different in society (Retnowaty, 2019). Miss and sir are usually used to respect someone that higher than us.…”
Section: Temporal Deixis Datamentioning
confidence: 99%
“…Deixis can be found in many areas like speech (Asmarita & Haryudin, 2019), song (Sitorus & Fukada, 2019), or novels with a different culture (Khalili, 2017). Speech delivered by a country leader, a business leader, or a community leader may be problematic when the audience has difficulty understanding the context and what reference the speaker intends to express (Retnowaty, 2019). Some public speakers do point when they speak in front of many people (Kurniadi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…She concluded that gestural deictic expression is more dominant than the symbolic one. Meanwhile, Retnowaty (2019) focused on analyzing Donald Trump's speech to UN General Assembly using Yule's and Levinson's theories. The results show that the most frequent deictic expression used by Donald Trump is the person deixis.…”
Section: Introductionmentioning
confidence: 99%